Innate immunity in pancreatic cancer: Lineage tracing and function - Ye, Longyun; Shi, Saimeng; Chen, Wei (Frontiers in Immunology, 2023)
Increasingly, patients with gastrointestinal tumors can benefit from immunotherapy, but not patients with pancreatic cancer. While this lack of benefit has been attributed to lower T-cell infiltration in pancreatic cancer, other studies have demonstrated the presence of numerous T cells in pancreatic cancer, suggesting another mechanism for the poor efficacy of immunotherapy. Single-cell RNA sequencing studies on the pancreatic cancer immune microenvironment have demonstrated the predominance of innate immune cells (e.g., macrophages, dendritic cells, mast cells, and innate immune lymphoid cells). Therefore, in-depth research on the source and function of innate immune lymphocytes in pancreatic cancer could guide pancreatic cancer immunotherapy.